Economic potential assessment of neodymium recovery from Malaysia e-waste resource - Joseph, C. V.; Mohd Yunus, M. Y.; Ismail, N. A.; Kanthasamy, R. (Elsevier Ltd, 2019)
Neodymium (Nd) is one of the core rare earth element (REE) which is in high demand globally and possesses huge economical advantage. However, Nd has been predicted to be in a great supply risk in the near future due to the dominant production and reserve controlled by China. Thus, the worldwide REE industry players nowadays look for alternative resources to further expand the scopes of REE supply. One of the potential sources is e-waste. Strengthening the recovery activity from e-waste streamlines could provide not only economically beneficial but more importantly may considerably lessening the environmental impact as a result of e-waste disposal. Hence, this study is proposed to study the economic potential assessment of recovering Nd which focusing on the Malaysia context. There are three Nd recovery processing models discussed - a) Nd extraction using P350 system b) Nd extraction using HDEHP-HCl system and c) Nd extraction using EHEHPA-HCl system. The analysis mainly highlights the amount of optimum economic gain by means of revenue index of each processing route as well as conducting cost-benefit analysis based on a set of specified investment performance targets of the selected processing. The results show that the P350 extraction system is the most feasible system with optimum revenue return for neodymium recovery of Malaysia from e-waste resource.